Article Overview : Prediabetes - Sri Meutya; Mumtaz Alvira (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Prediabetes is a condition characterized by impaired glucose tolerance. According to the American Diabetes Association (ADA), impaired glucose tolerance is defined as a 2-hour plasma glucose value ranging from 140 mg/dL to 199 mg/dL during an oral glucose tolerance test (OGTT) with a 75-gram glucose load. The World Health Organization (WHO) has projected that in the year 2000, the number of individuals over the age of 20 with diabetes was 150 million, and within a span of 25 years, by 2025, this number is expected to increase dramatically to 300 million. The purpose of this article is to comprehensively understand Prediabetes. The methods employed include a systematic summary of 20 data sources to consolidate information regarding prediabetes. The findings encompass the definition, etiology, epidemiology, classification, pathophysiology, diagnosis, and management of prediabetes.